Increase of Firmness of the Metall-Cutting Tool on the Basis of Removal of Internal Tension in Replaceable Cutting Insert; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Chuykov R. S. (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen